Intrinsic fluorescence of nucleobase crystals. Issue 2 (13th December 2022) - Aizen, Ruth; Arnon, Zohar A.; Berger, Or; Ruggiero, Antonella; Zaguri, Dor; Brown, Noam; Shirshin, Evgeny; Slutsky, Inna; Gazit, Ehud
Abstract : Nucleobase crystals exhibit intrinsic fluorescence in the visible range and red edge excitation shift. Abstract : Nucleobase crystals demonstrate unique intrinsic fluorescence properties in the visible spectral range. This is in contrast to their monomeric counterparts. Moreover, some nucleobases were found to exhibit red edge excitation shift. This behavior is uncommon in the field of organic supramolecular materials and could have implications in fields such as therapeutics of metabolic disorders and materials science.